The Ambiguity in the Verb Words in the Epic - Khamdamova, Hanifa (RA Journal of Applied Research, 2021)
This article describes the historical and etymological aspects, lexical and semantic nature of the words used in the epos “Rustamkhan” and their ambiguous features. Polysemy plays a significant role in any language. Linguistic richness is measured not only by words and phrases, but also by the lexical meanings of words. The ambiguity of words is that the phenomenon of polysemy has its place in the richness of language [1, p. 3]. Based on the same principles, we tried to study the polysemous words used in the text of the epic “Rustamkhan” from a semantic, lexical-grammatical and genealogical point of view.